DEVELOPING ENGLISH READING TEXT MATERIALS IN CULINARY FOR VOCATIONAL SCHOOL - Chrishna Sianturi and Muhammad Natsir (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study is aimed to develop English reading text materials about describing people, food and culinary spot based on students’ needs of Culinary Art. This study was conducted by using Research and Development (R&D). The subject of this research was class X SMKN 10 Medan consisting of 32 students. The language skill was concerned on reading comprehension, particularly in descriptive text. Qualitative data consist of syllabus, lesson plan, and existing teaching materials. Instrumentation for collecting data were questionnaire, interview and existing materials. After analyzing the data, the writer got the students’ need in learning English in term of vocation that they have through questionnaire and interview. After the students’ need had been analyzed, the new reading materials was developed. The developed teaching materials were related to the vocation that the students had; it was culinary art. The development of materials followed six stages; those were gathering information and data, analyzing data, designing new reading material, validating new reading material, revising new reading material, and final product revision. Based on the result of experts’ validation, the developing English reading text materials was equipped with adding one example in each exercise, adding the representative picture in each chapter and adding the generic structure of descriptive text on the reading text. Based on the result of the study, it can be concluded that developing English reading text materials is appropriate (4.32 = 86.55%) to use by the students of Culinary Art.